Nanoparticle silicalite-1 crystallization as monitored by nitrogen adsorption - Tokay, Begüm; Karvan, Oğuz; Erdem-Şenatalar, Ayşe (Elsevier BV, 2010)
Abstract Nanoparticle silicalite-1 crystallization from clear solutions was followed by nitrogen adsorption at 77 K, applied to the products collected from the synthesis solution at different times. Isotherm data were analyzed by t-plot/BET, density functional theory (DFT), and Saito–Foley methods. Variation in the micropore and mesopore/external areas and volumes of the products with time, were in strong agreement with a recent study, which indicated that nucleation that took place after an induction time, was accompanied by an aggregation of a population of smaller particles. A sharp decrease in external surface area was observed parallel to a significant increase in the micropore area of the solid product at this stage of synthesis, when a sudden jump in the effective diameter of the nanoparticles in solution was recorded. Although earlier appearance in the solid products, of small amounts of particles/regions with pore sizes in a range including the pore sizes of silicalite-1, was indicated by both the DFT and Saito–Foley analyses, variation of the Saito–Foley median diameter with synthesis time provided a clear evidence of the significance of this “induction time”, after which particles could grow at a constant linear rate. Nitrogen adsorption at 77 K was shown to be a useful tool to monitor the nucleation and crystal growth of silicalite-1 nanoparticles.